Motif Masyarakat Berolahraga - Zihan Novita Sari; Hengki Kumbara; M. Taheri Akhbar (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2022)
The purpose of this study was to determine the community's motives for exercising in Kambang Iwak, Palembang City. The research method used is the descriptive method. Data collection using a questionnaire instrument. The research data were analyzed using the percentage formula. The results of the study, based on internal motives who answered "Yes" obtained a score of 681 or 85.125, and those who answered "No" obtained a score of 119 or 14.875%. and the results based on external motives who answered "Yes" obtained a score of 695 or 86.875% and those who answered "No" obtained a score of 105 or 12.5%. In conclusion, external motives play a very important role in exercising at Kambang Iwak Palembang City by obtaining a higher score of 86.875%. Keywords: Community Exercise Motive The purpose of this study was to determine the community's motives for exercising in Kambang Iwak, Palembang City. The research method used is the descriptive method. Data collection using a questionnaire instrument. The research data were analyzed using the percentage formula. The results of the study, based on internal motives who answered "Yes" obtained a score of 681 or 85.125, and those who answered "No" obtained a score of 119 or 14.875%. and the results based on external motives who answered "Yes" obtained a score of 695 or 86.875% and those who answered "No" obtained a score of 105 or 12.5%. In conclusion, external motives play a very important role in exercising at Kambang Iwak Palembang City by obtaining a higher score of 86.875%. Keywords: Community Exercise Motive